Systemic management sustainable human interactions with ecosystems and the biosphere - Fowler, Charles W. (Charles Winsor), 1941- (Oxford : Oxford University Press, 2009)
'Systemic Management' describes a holistic, objective and universally applicable form of management, providing a framework for addressing environmental challenges such as global warming emergent diseases, deforestation, overpopulation, the extinction crisis, pollution, over-fishing, and habitat destruction.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Nature -- Effect of human beings on; Ecosystem management; Ecosystem management -- Bering Sea Region -- Case studies; Conservation of natural resources